Psychological Stress among Dental Students at Al-Iraqia University after Corona Virus Pandemic - Mohammad M. Abdulrazzaq1 , Marwah M. Adnan2 , Zeena T. Abdulhadi Al-Ani3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Aim of the Study: Among undergraduate dental students at Al-Iraqia University after “Covid-19” pandemic, this study was done in order to evaluate the amount of psychological stress between them. Materials and Method: By the use of the General Health Questionnaire (GHQ-12), Psychological stress was evaluated among (305) students who asked to fill completely the supplied questionnaires. Results: The highest level (22.3%) was found at the 1st stage, and generally among female higher than male, (60.9%) scored more than 3 on the (GHQ- 12) vs. (38.8%) for male, at p=0.05 which was considered to be statistically significant. Conclusion: Despite the changes in the curriculum and the gradual increase in the number of students. The different sources of stress from the year 2020 were mostly unaltered in our study. To minimize stress among dental students during certain conditions further studies is needed.